2007
DOI: 10.1007/s11340-007-9080-6
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of Stiffened Thin-Walled Truncated Cones Subjected to External Pressure

Abstract: The results of external air pressure buckling tests of thin-walled, truncated conical steel shells are presented, along with a description of the equipment developed for the testing program. The testing was conducted in support of Sandia National Laboratories Z-Pinch Inertial Fusion Energy Proof-of-Principle power plant design. Optimized stiffening ring locations were determined by using the finite element method, and were then tested, indicating an experimental improvement in initial buckling pressure of more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…During this series of tests, shells with different stiffener spacing, stiffener geometry and varying shell thickness with different taper ratio were investigated. Barkey et al [77] at Sandia National Laboratory studied the buckling behavior of thin-walled truncated cones made from ASTM 1008 steel. Cones were subjected to external pressure and formed a study into the structural integrity of a fusion related component.…”
Section: Buckling Experiments On Externally Pressurized Conesmentioning
confidence: 99%
“…During this series of tests, shells with different stiffener spacing, stiffener geometry and varying shell thickness with different taper ratio were investigated. Barkey et al [77] at Sandia National Laboratory studied the buckling behavior of thin-walled truncated cones made from ASTM 1008 steel. Cones were subjected to external pressure and formed a study into the structural integrity of a fusion related component.…”
Section: Buckling Experiments On Externally Pressurized Conesmentioning
confidence: 99%
“…Tests on 19 steel, seamless cones obtained by using the metal spinning, are described in Ref. [87]. The base diameter of all models was 500 mm and the wall thickness was 0.635 mm.…”
Section: Externally Pressurized Conesmentioning
confidence: 99%
“…Singer studied buckling behavior of the cones under axisymmetrically applied external pressure [5] and he also found the correlation of the conical shells with the equivalent cylindrical shells to predict the critical pressure [6]. Buckling of stiffened and unstiffened thin-walled truncated cones subjected to external pressure was studied and reported by Barkey et al [9]. The results of 19 specimens indicated that the buckling pressure values obtained from the tests were 60-80% of the FE and analytical calculations.…”
Section: Introductionmentioning
confidence: 96%